Metropolitan Fleet Car. Ein Modell zur Flexibilisierung von Flotten für Fuhrparks und Carsharing. - Johnsen, Doris; Meyer, Uli (Deutscher Verkehrs-Verl., 2005)
Die Idee, Fahrzeugflotten mit komplementären Nutzungsstrukturen zu kombinieren, um so eine Effizienzsteigerung zu erreichen, erscheint nahe liegend. Die Umsetzung einer solchen Idee erwies sich jedoch als wesentlich voraussetzungsvoller als erwartet. difu

The MFC (Metropolitan Fleet Car) model seeks to combine the fleet of vehicles of companies specializing in car sharing with that of commercial firms. Cars available for sharing tend to be used over the weekend whereas commercial vehicles are in use during the working week. A combined usage could conceivably lead to a reduction in the size of separate fleets of vehicles and thus achieve more flexibility. Making this concept a reality has proved more difficult than expected. It is necessary to meet certain conditions fully prior to adopting the MFC model. Notably in Berlin, where its implementation - as part of a project sponsored by he EU - began with high expectations, a number of problems emerged unexpectedly. The report features the obstacles that ad to be overcome and the rate of success achieved from implementing this model. difu
Keywords: Straßenverkehr; Verkehr; Autoverkehr; Kraftfahrzeug; Fuhrpark; Organisationsstruktur; Firmenfahrzeug; Autoverleih; Car-Sharing; Cash-Car; Fuhrparkmanagement; Koordinierung; Vermarktung; Mobilitätskonzept; Autofahrer